Stock Market Integration in the ASEAN-5 - Prukumpai, Suthawan; Sethapramote, Yuthana (Asian Journal of Applied Economics, 2018)
This paper aims to investigate the degree of stock market integration in the ASEAN region, both internally and externally, in relation to global markets: in particular those of the United States and Hong Kong. There are three main findings in the paper. First, this paper investigated long-run integration using Engle and Granger cointegration and found that evidence of cointegration is stronger in the case of internal region integration than in the external region one. Moreover, the cointegration tests with structural breaks revealed that there was additional supporting evidence for the long-run relationship among ASEAN-5 markets. In most cases, structural breaks were found during the period of the Asian financial crisis in 1997. Second, the results of the short-run market correlations showed that Singapore had the highest co-movement with global markets, especially that of Hong Kong. In addition, Indonesia appeared to be less integrated with other markets, especially outside the region. Moreover, the time-varying patterns of short-run correlations were found to show an increasing trend, both inside and outside region. Finally, this paper found that financial market factors, i.e. the size of market capitalization and the degree of exchange rate volatility, were important in determining the level of stock market integration. Trade links were another important factor; bilateral trade between specific partners yielded stronger evidence for determining the level of integration than the trade openness of each country. Moreover, the similarity in fundamental macroeconomic factors only had a minor effect on determining the degree of stock market integration.